Sandinista : Carlos Fonseca and the Nicaraguan Revolution - Zimmermann, Matilde, 1943- (Book collections on Project MUSE., 2000)
The life and ideas of Carlos Fonseca Amador, founder of the Sandinista National Liberation Front (FSLN).